Development of a test method for adhesive tapes certification and application - Linløkken, Tore Kolstad; Geving, Stig; Hrynyszyn, Bozena Dorota (Frontiers in Built Environment, 2024)
Sufficient airtightness of a building envelope is important both to ensure the overall energy efficiency of a building and to prevent moisture-related damage to the structure. Air leakages typically occur in the context of joints and perforations in vapor barriers installed inside walls and roofs. It is essential to give proper attention to details to achieve sufficient airtightness of building envelopes and joint’s durability. Sealing such building details with durable solutions is essential for ensuring sufficient airtightness overall. In recent years, adhesive tapes have increasingly been used for this application. However, there remains uncertainty regarding its performance in the long-term. The study offers an overview of the current state of the art by incorporating findings from a literature review including an analysis of established methods currently being used for evaluation of tape joint durability, as well as other experimental test methods. The aim of research presented in this paper is to contribute to the development of a test method with sufficient accuracy, reproducibility, and repeatability to be used in the development and certification of tape products and systems. Although the method in development displays limitations in terms of reproducibility, it is regarded as a promising concept. Through further development, the method is believed to be suitable for potential integration into wider evaluation programs addressing adhesive tape durability, supplementary to existing methods.